Unified approach of generalized inverse and its applications - Ahmed, Mohammad Maruf (BRAC University, 2010)
This paper deals with Unified Approach of Generalized inverse (g-inverse) and its applications. General approaches of generalized inverses with a special convergence are discussed. Derivation of g-inverse by using minimal polynomial is shown. Mathematica codes are used in these examples. Special derivations of g-inverses using Contour integration are given. G-inverse has been applied in network theory and to optimize problems.